Near-IR activity of hybrid solar cells: enhancement of efficiency by dissociating excitons generated in PbS nanoparticles - Guchhait, Asim; Rath, Arup Kumar; Pal, Amlan J. (Applied Physics Letters, 2010)
Photovoltaic devices based on PbSnanoparticles remained inactive in the near-IR region due to a not-so-favorable energy band-diagram that does not allow dissociation of excitons generated in PbS. In this work, with the introduction of nanostructures in the PbS-based hybrid system, we show an enhancement of photovoltaic performance in both visible and near-IR regions. The addition of increases the power conversion efficiency from 0.006% to 0.12%. With the aid of energy band-diagram, we show that excitons generated in PbS even in the near-IR range can now become dissociated to yield photocurrent in the external circuit.